Massive Transfusion in a case of Hepatocellular Carcinoma - Bodade, Anand Gulabrao; Rajadhyaksha, Sunil B. (Indian Journal of Case Reports, 2020)
The mortality in massive transfusion is high due to many associated complications. We share our experience with massive blood transfusion in a young patient with 71 units of blood products transfused within 24 hours and 90 more blood components required in subsequent days. The case highlights the importance of massive transfusion protocol to improve clinical outcomes in the patient and judicious use of precious blood units. Blood transfusion services and the clinical team should have good communication and coordination to deal with such situations. Furthermore, in view of cost, constant increased demand, urgency, limited availability and risk of associated infections, more research in the area of blood substitutes is highly re-commanded. This case report also emphasizes on future research to make blood substitute with more similarities and minimum complications.